Formation of a rotating jet during the filament eruption on 2013 April 10–11 - Filippov, B.; Srivastava, A. K.; Dwivedi, B. N.; and et al (Oxford University Press, 2015)
We analyse multiwavelength and multiviewpoint observations of a helically twisted plasma jet formed during a confined filament eruption on 2013 April 10-11. Given a rather large-scale event with its high spatial and temporal resolution observations, it allows us to clearly understand some new physical details about the formation and triggering mechanism of twisting jet. We identify a pre-existing flux rope associated with a sinistral filament, which was observed several days before the event. The confined eruption of the filament within a null-point topology, also known as an Eiffel tower (or inverted-Y) magnetic field configuration results in the formation of a twisted jet after the magnetic reconnection near a null point. The sign of helicity in the jet is found to be the same as that of the sign of helicity in the filament. Untwisting motion of the reconnected magnetic field lines gives rise to the accelerating plasma along the jet axis. The event clearly shows the twist injection from the pre-eruptive magnetic field to the jet.
Keywords: Sun: activity; Sun: filaments, prominences; Sun: magnetic fields